2019
DOI: 10.51415/ajims.v1i1.809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Computer Assisted Instruction on Teaching of Self Reliance Skills for Sustainable Entrepreneurship Development among Undergraduate Social Studies Students in Kaduna State

Abstract: This study explored the effect of Computer Assisted Instruction (CAI) on the teaching of selfreliance skills for sustainable entrepreneurship development amongst undergraduate Social Studies students in Kaduna State, Nigeria. Three (3) research objectives, questions and null hypotheses guided the study. A quasi-experimental research design was employed. The Self Reliance Skills Performance Test (SERSIT) was used for data collection. Mean, standard deviation, t-test and two-way ANOVA statistics were used. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The results of the study conform to the findings of the previous studies that CAI is a helpful tool in increasing students' academic performance (Bonsu et al, 2020;Ekpenyong & Akwagiobe, 2018;Keane, 2018;Lawal & Abdullahi, 2019;Nwaubani et al, 2014;Raghaw et al, 2018;Usman, & Madudili, 2020;Wahyuni, 2016;Xefteris et al, 2019).…”
Section: Academic Performance Of Students Before and After The Application Of Caisupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the study conform to the findings of the previous studies that CAI is a helpful tool in increasing students' academic performance (Bonsu et al, 2020;Ekpenyong & Akwagiobe, 2018;Keane, 2018;Lawal & Abdullahi, 2019;Nwaubani et al, 2014;Raghaw et al, 2018;Usman, & Madudili, 2020;Wahyuni, 2016;Xefteris et al, 2019).…”
Section: Academic Performance Of Students Before and After The Application Of Caisupporting
confidence: 89%
“…Extensive scholarly literature showed the effectiveness of CAI as a teaching strategy (Adigun, 2020;Cassady et al, 2018;Guo, 2018;Hawkins et al, 2017;Hendikawati et al, 2019;Kim et al, 2017;McKissick et al, 2018;Onah et al, 2020;Priskilla, 2018;Root et al, 2017;Syahmaidi et al, 2021;Tomesko et al, 2017;. Furthermore, several studies also revealed the effectiveness of CAI in SS instruction (Bariham, 2019;Bonsu et al, 2020;Ekpenyong & Akwagiobe, 2018;Keane, 2018;Lawal & Abdullahi, 2019;Nwaubani et al, 2014;Usman, & Madudili, 2020). In the Philippines, CAI is also found useful in enhancing students' academic achievement (Rosali, 2020), enhancing comprehension (Kabigting, 2020), and being an effective tool for teaching (Marquez, 2017;Suson & Ermac, 2020).…”
Section: Introductionmentioning
confidence: 99%